Pengaruh Kepemimpinan Terhadap Kinerja Pegawai Dikantor Kecamatan Teras Kabupaten Boyolali - Harjanta, Jana - (Transformasi, 2012)
AbstractHuman Resources (HR) is one of the most significant assets for any organization.Therefore it is necessary to continue to be addressed and be empowered in order to obtain aprofessional apparatus. In explaining leadership, author use the Leadership Behaviordeveloped by Garry Yulki (1998). Because this theory can provide a description of the perceiveddepth and also can explain how the factor of leadership can provide a significant effect onperformance. This suggests that leadership have a positive and significant relationship withemployee performance. So it can be concluded that the better leadership then the employee willget better performance anyway. A working hypothesis (ha) supported, proven and accepted thetruth.Key Words: Leadership, Performance